The existence of e-commerce for digital natives : (relation between shopping motives and Konsumtive behavior) - Mochamad Afandi As'ad Rochani; Emma Yunika Puspasari (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2023)
This study aims to find out about the existence of e-commerce for digital natives, the relationship between shopping motives and consumptive behavior, this research uses a qualitative approach with an intrinsic case study type, this research refers to informants, namely students of economics education class of 2019, Malang State University. This study used a purposive sample and a snowball sample. The analytical method used in this study is the data analysis method with the Miles and Huberman model and the data analysis method with the Spradley model. The results of this study indicate that the relationship between shopping motives and consumptive behavior is related, this is in accordance with the answers of the informants who explained that online shopping helps in everyday life but if done with high intensity it can make a person enter into consumptive behavior which has an impact bad for that person because buying goods is no longer a need but a mere wish. Interview data shows that most informants choose completeness of products in online shopping while the purchasing criteria that are carried out prefer goods that are suitable and suitable, this is categorized as consumptive behavior, if it is carried out continuously without more mature consideration and enters into addictive consumptive behavior.